2018
DOI: 10.1016/j.msea.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Laser powder bed fusion of Hastelloy X: Effects of hot isostatic pressing and the hot cracking mechanism

Abstract: Hastelloy X is the trademark for a nickel-based, high-temperature superalloy that is increasingly applied in gas turbine engines because of its exceptional combination of oxidation resistance and high-temperature strength. The superalloy suffers from hot cracking susceptibility, however, particularly when processed using additive manufacturing and laser powder bed fusion (LPBF). This paper systematically studies for the first time the effect of post-treatment hot isostatic processing (HIP) on the microstructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 200 publications
(45 citation statements)
references
References 29 publications
1
41
2
1
Order By: Relevance
“…It should be noted that the opened pores exhibited irregular shapes rather than the circular shapes that were observed on the sectioned surface. The dendritic features were not observed in the fracture surfaces, which differs from the previous findings of a previous study on additive-manufactured HX alloys [11]. In that study, cleavage-like surfaces were observed, indicating that the columnar grains were elongated along the loading direction.…”
Section: Experimental Validationcontrasting
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the opened pores exhibited irregular shapes rather than the circular shapes that were observed on the sectioned surface. The dendritic features were not observed in the fracture surfaces, which differs from the previous findings of a previous study on additive-manufactured HX alloys [11]. In that study, cleavage-like surfaces were observed, indicating that the columnar grains were elongated along the loading direction.…”
Section: Experimental Validationcontrasting
confidence: 99%
“…In that study, cleavage-like surfaces were observed, indicating that the columnar grains were elongated along the loading direction. This difference may be explained by the fact that the tensile samples were horizontally built in the present study (perpendicular to the loading direction), while the specimens used in [11] were fabricated vertically (parallel to the loading direction).…”
Section: Experimental Validationmentioning
confidence: 96%
See 1 more Smart Citation
“…Additive manufacturing (AM), a rapidly developing and advanced manufacturing technology, provides an integrated way to fabricate three-dimensional complex-shaped components from computer-aided design models [7][8][9]. Among the most advanced AM technologies, selective laser melting (SLM) is a widely used process for manufacturing complex metallic parts [10][11][12]. Several recent studies have reported the microstructure and mechanical properties of SLM-fabricated AlSi10Mg alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The selected material was Hastelloy C-22. This alloy presents excellent corrosion behavior as well as mechanical properties, being commonly employed in the industrial sectors [18][19][20][21][22][23]: Chemical, petrochemical, aerospace, etc.…”
Section: Introductionmentioning
confidence: 99%